Polydiacetylene stabilized gold nanoparticles – extraordinary high stability and integration into a nanoelectrode device. Issue 125 (1st December 2015) - Liffmann, R.; Homberger, M.; Mennicken, M.; Karthäuser, S.; Simon, U.
Abstract : A new diacetylene containing photopolymerizable ligand molecule was developed, and tailored for applications in nanoelectronic devices based on gold nanoparticles. Abstract : A new diacetylene containing photopolymerizable ligand molecule was developed, and tailored for applications in nanoelectronic devices based on gold nanoparticles. This ligand molecule consists of a thiol group, a diacetylene unit and a terminal carboxylic group. The thiol group guarantees preferred binding to the gold nanoparticles surface whereas at the same time the carboxylic group enables electrostatic stabilization. Applying this ligand molecule, gold nanoparticles in the size range of 12–13 nm were prepared. The diacetylene unit was polymerized upon UV irradiation leading to a polymeric ligand shell. Investigations including colloidal stability towards NaCl, DTT displacement reactions, and temperature were performed and indicate an extraordinary high degree of steric and electrostatic stabilization. Individual or at least a few of these particles were immobilized in between nanoelectrodes, thus forming nanoelectronic devices, which were characterized by transport measurements.